LAJU PENDINGINAN PADA MESIN PENDINGIN MENGGUNAKAN R-12 DAN MC-12 - Yuyuk Darma Putra K. Sitinjak; Frans Palobo Sappu; Hengky Luntungan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
enMost refrigeration system using synthetic refrigeration R-12, R-22, R-134, and R-600a. Synthetic refrigeration has many good characteristics, among others, not easy to burn, no poisoned, and easy to get. However, synthetic refrigeration has negative effects for environment. It can brokeÂ our ozone layer and make global warming. The using of hydrocarbon as refrigerant is one of the solution to handle these problems. An experiment is done using unit SN 1016-1-149-1 cooler machine in mechanical laboratory in Sam Ratulangi University in Manado. Data is taken after completedÂ the unit preparation. Analysis is done by comparing the cooling rate beetwen R-12 and MC-12. The average cooling rate of R-12 cooler are and respectively using air and water cooling media. In a serial of three experiments, The average electric current used in the unit are 0,75 A and 0,74 for air and water media respectively using of R-12 and Of MC-12 refrigerant . The average cooling capacity of MC-12 is . Then, faund that MC-12 cooler capacity by air and water media is bigger than R-12 cooler capacity by air and water media. Key words : R-12, MC-12, Cooler Speed